PENINGKATAN HASIL BELAJAR OPERASI HITUNG CAMPURAN BILANGAN BULAT DENGAN PENDEKATAN CTL DI KELAS IV SD - Chandra, Daswil; Ahmad, Syafri; Harun, Mardiah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe learning outcomes of operations with approach Contextual Teaching and Learning (CTL) in the class IV SD Pembangunan Laboratorium UNP. The type of research conducted is classroom action research with qualitative and quantitative approaches. The results of the study showed that the assesment of cycle one learning planning was eighty two point one percent and cycle two ninety two point nine percent. Assessment of the implementation of cycle one teacher activities is eighty point four percent and cycle two is ninety six point four percent. Assessment of the implementation of cycle one student activities is seventy five percent and cycle two is ninety six point four percent. Assessment of student learning outcomes cognitive aspects of cycle one average value is seventy two point seventy eight and cycle two is ninety two point twenty two. In the affective aspect of the cycle one the average value is seventy five point twenty and cycle two eighty three point thirty nine. Whereas for the psychomotor aspect of cycle one the average value is seventy four point eighty four and cycle two eighty seven point zero six. Based on the results of the study, it was concluded that the CTL approach can improve the learning outcomes of calculating the integer mixture of fourth grade students in the class IV SD Pembangunan Laboratorium UNP.